Can empowering leadership promote employees’ pro-environmental behavior? Empirical analysis based on psychological distance - Yue, Ting; Gao, Chenchen; Chen, Feiyu; Zhang, Lan; Li, Mengting (Frontiers in Psychology, 2022)
Leadership styles, especially empowering leadership, affect the psychological relationship between employees and organizations, and then affect employees’ positive behavior in the organization. In this research, we studied the effects of empowering leadership and psychological distance on employees’ pro-environmental behavior and explored the mechanism of green organizational climate (GOC). By adopting correlation analysis, statistical analysis, and regression analysis, we conducted a multisource field study of 873 valid employee questionnaires to verify our theoretical model. The results showed that empowering leadership had a significant positive impact on psychological distance and employees’ pro-environmental behavior; and psychological distance played a partly intermediation role in the relationship between empowering leadership and employees’ pro-environmental behavior. Moreover, GOC can promote employees’ pro-environmental behavior, but it cannot regulate between psychological distance and employees’ pro-environmental behavior. The findings obtained some intriguing insights that could help to better guide employees toward pro-environmental behavior.